Penguatan Literasi Digital dalam Pembelajaran Matematika Melalui Aplikasi Geogebra pada Siswa SMP Darul Ulum 2 Jombang - Dinarti, Siti; Masruroh, Faridatul; Herninda, Amalia Revy (Universitas Islam Lamongan, 2025)
This community service activity aims to strengthen the digital literacy of students at Darul Ulum 2 Jombang Junior High School through the use of the GeoGebra application in mathematics learning. In this digital age, digital literacy is an essential competency, and its integration into mathematics learning has been proven to improve understanding of abstract concepts. The implementation method adopts the Participatory Action Research (PAR) approach with five stages: to know, to understand, to plan, to act, and to change, emphasising active collaboration with the school and students. Evaluation was conducted using pre-tests and post-tests to measure improvements in digital literacy and mathematical understanding, as well as a questionnaire on participants' responses to the method, materials, and facilitators. The results of the pre-test and post-test showed a significant increase in the average student scores, indicating that the training successfully improved their knowledge and skills in both areas. Specifically, the indicator for the ability to use GeoGebra showed the highest increase. Participants' feedback on the method, materials, and facilitators was also very positive, highlighting the effectiveness of the hands-on approach and the relevance of the materials presented. The quality of competent and responsive facilitators was also a key factor in the success of the programme. This initiative successfully demonstrated that the effective integration of the GeoGebra application can be a powerful strategy for enhancing students' digital literacy and mathematical understanding. Additionally, the use of this technology successfully increased students' interest and motivation to learn, equipping them with relevant digital skills to tackle current and future learning challenges.